CASE REPORT: AFIRMASI POSITIF PADA HARGA DIRI RENDAH SITUASIONAL PASIEN FRAKTUR FEMUR - Agustin, Ike Mardiati; Handayani, Sri (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Patients with fractures will experience a decrease in physical condition, dependence on medical actions that result in changes in the patient's life, disability and role change due to physical limitations can raise the psychological problem of low situational self-esteem. The purpose of this paper describes the results of the application of positive affirmation therapy on low self-esteem situational patients fracture of the femur. The methodology used was analytic descriptive with case study approach on 5 patients of femur fracture who experienced low situational self esteem. Results The application of positive affirmation therapy is effective in lowering the symptoms of low self-esteem situational symptoms with medical diagnoses of femoral fracture with a decrease of cognitive, affective, physiological, behavioral and social signs. A positive affirmation therapy recommendation is recommended for patients with physical problems with psychological low self-esteem situational problems